(untitled) (Innovative professional education, 2023)
War is a traumatic event that causes feelings of helplessness and insecurity, affecting a person’s way of thinking and their attitude to the world, causing chronic stress disorders. Participation in educational processes has acquired a new emotional color for all of their participants. This is a difficult test both for teaching staff, who despite the stress and danger continue to conduct classes online, and for students, some of whom were forced to leave their homes. The realities of on-line training of vocational education seekers are considered, and ways of solving problems are proposed.